PENGEMBANGAN GIS HYDRANT KOTA BATAM (BATAM WEB-GISH) - sitohang, sunarsan (Journal Information System Development (ISD), 2019)
The development of information technology is currently very rapid, thus it is possible to be used for positive things such as helping human work. One of human's jobs is as firefighting personnel. Fire disasters often occur in places, cities, and countries. Batam City is one of the most densely populated cities where residents live in housing, lots and illegal houses (RULI) and their land contains bauxite. This condition is one of the factors causing the fire disaster. The Batam City Government has provided several hydrant facilities as a source of water for fire disaster management. Hydrants in Batam City are very adequate, but the management has not utilized information technology, so that if a fire occurs in one location, firefighters must manually search for the hydrant location. Based on this problem, researchers are interested in building a web Geographic information system hydrant (web-GISH) so that hydrants managed by the Batam city government are mapped on the web-GISH. The development of this website will be done by collecting hydrant location data in the form of latitude and longitude data, designing website interfaces, building a hydrant database and building web-based applications by utilizing google maps service as a provider of hydrant location information. With the existence of a special map of hydrant locations in the city of Batam, it indirectly helps firefighting personnel in handling fire disasters.